Photocatalytic degradation of Rhodamine B using graphitic carbon nitride photocatalyst - Yadav, A. A.; Kang, Seok-Won; Hunge, Y. M. (Journal of Materials Science: Materials in Electronics, 2021)
In this work, a graphitic carbon nitride (g-C 3 N 4 ) photocatalyst was synthesized by pyrolysis of melamine. The effect of different synthesis temperatures on the structural, morphological, and optical properties of the g-C 3 N 4 photocatalyst was investigated. X-ray diffraction and Raman spectroscopic analyses confirmed the formation of the g-C 3 N 4 photocatalyst. The elemental composition and valence states of the g-C 3 N 4 photocatalyst were studied using X-ray photoelectron spectroscopy. A specific surface area of 25.45 m 2 /g was measured using the BET technique. UV–Vis spectroscopy showed that the g-C 3 N 4 photocatalyst exhibited good absorbance in the ultraviolet and visible regions. The photocatalytic performance of the g-C 3 N 4 photocatalyst was tested for the degradation of Rhodamine B under sunlight illumination.